Welding Current and Shielding Gas Flow Rate Effect to The Intermetalic Layer Formation of Tungsten Inert Gas (Tig) on Dissimilar Metals Weld Joints Between Galvanized Steel and Aluminium Aa 5052 By Using Al-Si 4043 Filler - Gilang Sigit Saputro; Triyono .; Nurul Muhayat (Universitas Sebelas Maret, 2017)
Tungsten Inert Gas welding of galvanized steel-aluminium useful for weight reduction, improve perform and reduce cost production. The effect of welding parameters, welding current and shielding gas flow rate on the intermetallic formation and hardness of dissimilar metals weld joint between galvanized steel and aluminium by using AA 5052 filler was determined. In this research, welding speed was consistent kept. The welding parameters were obtained by using welding currents of 70, 80 and 90 A, shielding gas flow rate of 10, 12 and 14 litre/min. The intermetallic layer thickness increased by welding currents of 70 A to 80 A, but then it dropped on 90 A. The higher of a shielding gas flow rate, the lower the thickness of the intermetallic layer. The higher of a welding current, the lower the hardness of weld. The higher of a shielding gas flow rate, the greater the hardness of weld. As a result,the maximum hardness by current variation of 70 A and a shielding gas flow rate of 14 Litre/min was 100.9 HVN.